Busulfan and melphalan as consolidation therapy with autologous peripheral blood stem cell transplantation following Children's Oncology Group (COG) induction platform for high‐risk neuroblastoma: Early results from a single institution. (16th December 2013) - Soni, Sandeep; Pai, Vinita; Gross, Thomas G.; Ranalli, Mark
Abstract Bu‐Mel as preparative therapy prior to autologous stem cell rescue was recently shown to be superior to the conventional CEM regimen for HR NBL in Europe. There are no data available on the feasibility and toxicity of Bu‐Mel as consolidation therapy following the COG‐type induction regimens used in North America. We report early complications and outcomes of patients with HR NBL who received Bu‐Mel for consolidation following COG‐based induction. Retrospective analysis of all patients who had received Bu‐Mel as preparative regimen prior to stem cell rescue for HR NBL was carried out. Toxicity, outcomes, and any delays to receiving radiation or anti‐GD2 antibody therapy were analyzed. Six patients undergoing PBSCT had received Bu‐Mel. The treatment was well tolerated. Mucositis was the main toxicity; three patients had developed neutropenia fever and none developed pulmonary toxicity. One patient had developed moderate SOS that responded to conservative management. All patients were able to receive and tolerate post‐transplant local radiotherapy and ch.14.18 anti‐GD2 antibody therapy without any delays. All patients are alive with no disease recurrence. The Bu‐Mel regimen is well tolerated and is feasible post‐COG‐type induction platform.